A study on factors that influence the collected indirect tax in Malaysia (service tax) / Tengku Ismail Tengku Ibrahim - Tengku Ibrahim, Tengku Ismail (2011)
This research was conducted to determine the factors influenced the collected Indirect tax in economy Malaysia. The main objective of this research is to study on the factors influenced the service tax collection in Malaysia regarding the government’s budget and spending. This research to indicate the relationship for each independent variable (Gross National Product, Unemployment and Inflation Rate) to ensure the positive relationship between them. This study was conducted based on the case study also known as secondary data collection and quantitative research method. Furthermore, the data collection has been calculated using SPSS software in order to show the relationship between all the variables for this research. Therefore, from this finding, we can say that service tax has related with the independent variables and shows the relationship between them. So, the two from three independent variables actually are part of the service tax collection because these are related with the research. Otherwise one independent variable is not related with the study and getting negative relationship